Penyuluhan Pencegahan Anemia pada Remaja Putri di Madrasah Tsanawiyah Swasta Pesantren Thawalib Padang - Melisa Yenti; Anggela Pradiva Putri; Suci Maisyarah Nasution; Shabrina Erika; Rahmad Fadhil Caesario (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Teenage girls are at risk of experiencing anemia because they menstruate every month. Anemia that is not treated immediately can negatively impact the short and long-term. In the long term, the impact of anemia can also affect pregnancy. Pregnancy with anemia will increase the risk of having a baby with a low birth weight and the risk that the child born will grow up to be stunted. So, women need to prevent anemia as early as possible. Education regarding the prevention of anemia has yet to be carried out at MTsS Pesantren Thawalib, and students have not taken Blood Supplement Tablets (BST) once a week. MTsS female students who menstruate every month are the right target group to be given education and health information related to preventing anemia. This service activity aims to increase female students' knowledge regarding anemia prevention. The methods used were counseling, putting up posters, giving BST, distributing pocketbooks, and distributing BST drinking calendars. The extension activities began with a pre-test and post-test to measure female students' knowledge before and after the education on anemia prevention. There was an increase in the average knowledge before 5.26 (pre-test) to 7.87 (post-test) after being given counseling with a p-value of 0.000. This shows that the anemia prevention education that has been carried out can increase the level of knowledge of female students. Students and schools should optimally utilize poster media, pocketbooks, and BST drinking calendars. With this service activity, female students can prevent anemia by regularly consuming BST once a week. Support is needed from MTsS Pesantren Thawalib Padang to monitor the student's compliance with BST consumption by checking the BST drinking calendar distributed to each student.